An extraordinary case of a hungry man: an unusual foreign body - A Case Report - Shi Nee T; Gopalan KN; Primuharsa Putra SHA (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
This case reports a rare case of accidental metal spoon swallowed by a normal adult which was successfully removed without complication under local anesthesia using a McGill forceps via laryngoscope. Aerodigestive foreign bodies are almost always managed by the otolaryngologist. This is the rarest foreign body of the metal spoon being swallowed by a normal adult by accident. Early removal is mandatory as this may lead to devastating complications.